Children Song Of Madura sebagai Media Promosi Pariwisata Madura - Fitriyono, Angga; Yuniar, Dias Putri; Anita, Rif’atul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
Madurese language songs have to be one of the promotional media tourism that needs to be developed with a purpose cultivate and advance Indonesian tourism with love of Indonesian folk songs . This era is a folk song especially regional song speak Madura is less popular to listen to or less common _ heard by the public . Introduction language and values - mark typical area can be channeled or depicted in lyrics , music or background from song. Introduction Language area And values wisdom need introduced since early , that is songs are played to children during school activities. Introduction in children especially child level _ early recognized _ through method sing . Sing is Wrong One method learning Which can used for support education character for older children early . Through the concept of making books and albums for children's songs in Madurese circles especially old children early can access songs anytime and anywhere course without limitation . Therefore this research seeks to do innovation which can be preserved culture wisdom local , preserve existence of children's songs, promote sector tourist Madura through study development model ADDIE. In the process of development and field trials carried out at RA Attahariyah Modung and TKM NU by getting mean values of 35, 36 and 38 indicate that this product managed to improve knowledge around tourism in Bangkalan , capabilities sing as well as ability Madurese language.